Principals best practice to conflict management at the excellent secondary schools, Malaysia - Salleh, Mohamad Johdi (2011)
This study discusses the best practice in conflict management among the principals of excellent secondary schools, Malaysia. The lists of the excellent schools were acquired from the Ministry of Education and the respective states department of education. The sample of the study was 510 respondents comprises of senior teachers, teacher administrators, teachers, and, counselors. The instrument used was survey questionnaire and data was processed using the Statistical Package for Social Science (SPSS) version 17.0 for Windows. The study was mainly based on Thomas and Kilmann (2008) conflict-handling modes comprises of competing, collaborating, compromising, avoiding and accommodating. It also referred to syūrā, nasihah,and, ta’āwun which prominent in Islamic management and administration that has been deeply appreciated and widely implemented since the prophet lifetime in managing conflict and making the best decision (Sarif, et al., 2004). The result shows that the principals’ best practice to conflict management was syūrāorcollaborating. It is hope that the findings of this study may guide the principals, teacher-administrators, educational leaders, teachers, and all group or individual in educational organization to manage conflicts wisely and successfully towards the harmonious working environment with optimum productivity in the era of globalization.